A Dutch Local Newspaper Digitised and Online in a Public–Private Partnership - van der Noord, Eddy (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
In a unique public–private partnership between the Frisian historical centre Tresoar and the publishers, the Dutch local newspaper Leeuwarder Courant, the oldest newspaper in the Netherlands, was fully digitised in 2006 and made available online at no cost to the user. With an average of 2 million page views each month, the website is a great success.